How urban Chinese parents with 14-month-old children talk about nanny care and childrearing ideals. Issue 4 (1st October 2020) - Zhang, Cong; Fong, Vanessa L.; Yoshikawa, Hirokazu; Way, Niobe; Chen, Xinyin; Lu, Zuhong; Deng, Huihua
ABSTRACT: Existing Western literature about childcare reveals parents hire nannies to play the role of surrogate mother, reflecting Western-held assumptions that a mother caring for her child is the optimal arrangement, with nannies hired to fill this void in their absence. Through analysis of semi-structured interviews with 10 urban Chinese families, our study reveals a departure from these assumptions when it comes to middle-class Chinese, who do not hire nannies as proxies for mothers or due to lack of alternative options. Rather, they seek out nanny care to supplement or enhance childcare provided by grandparents or stay-at-home mothers by building multi-caregiver coalitions in which resources and advantages are pooled to improve care quality. This study uses nanny care as a lens to explore these culturally divergent patterns and reveals that, unlike their Western counterparts, Chinese parents do not see exclusive maternal care for children as ideal or sufficient.